Methylprednisolone prevents bacterial translocation in thioacetamide-induced liver failure in rats - Harputluoğlu, Murat Muhsin Muhip; Temel, İsmail; Demirel, Ulvi; Seçkin, Yüksel; Aladağ, Murat; Otlu, Barış; Karadağ, Neşe; Özyalın, Fatma; Aydoğan, Nilay; Selçuk, Engin Burak (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Steroids have been shown to prevent intestinal oxidative stress. We investigated the effects of methylprednisolone on intestinal oxidative damage and bacterial translocation in thioacetamide-induced liver failure in rats. Materials and Methods: Group 1 (n=8) was the control group. In group 2 (n=8), the thioacetamide group, rats received 300 mg/kg intraperitoneal thioacetamide daily for 2 days. In group 3 (n=8), the thioacetamide+methylprednisolone group, treatment with methylprednisolone (30 mg/kg intraperitoneal) was commenced 48 h before the first dose of thioacetamide. In group 4 (n=8), the methylprednisolone group, the rats received only methylprednisolone (30 mg/kg intraperitoneal). Results: Serious hepatic and intestinal oxidative damage and high bacterial translocation frequencies were observed in the thioacetamide group compared with those of the controls. Bacterial translocation frequency in the thioacetamide+methylprednisolone group was significantly lower than that in the thioacetamide group (p Conclusion: Our findings suggest that methylprednisolone reduces bacterial translocation by preventing intestinal oxidative damage in this model of acute liver failure in rats. Cite this article as: Harputluoğlu MMM, Temel İ, Demirel U, et al. Methylprednisolone prevents bacterial translocation in thioacetamide-induced liver failure in rats. Turk J Gastroenterol 2017; 28: 394-400.